4=-4w+2(w-2)

Simple and best practice solution for 4=-4w+2(w-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4=-4w+2(w-2) equation:



4=-4w+2(w-2)
We move all terms to the left:
4-(-4w+2(w-2))=0
We calculate terms in parentheses: -(-4w+2(w-2)), so:
-4w+2(w-2)
We multiply parentheses
-4w+2w-4
We add all the numbers together, and all the variables
-2w-4
Back to the equation:
-(-2w-4)
We get rid of parentheses
2w+4+4=0
We add all the numbers together, and all the variables
2w+8=0
We move all terms containing w to the left, all other terms to the right
2w=-8
w=-8/2
w=-4

See similar equations:

| 10*8=12*x | | 7-2xx=-2 | | -2x^2+32x-290=0 | | 20=k/17 | | 4×(8-3a)=-2×(2+3a)+12 | | -8(v+-5)=-6v-20 | | 370=15n+85 | | 3z/2=2/6+4 | | f(-3,16)=-3,16^4-5(-3,16)^2+4 | | 2x+6=2(x+3 | | 16x-29+7=0 | | d+1.19=19.59 | | w-2.05=4.03 | | G(x)=3-5x-2x | | p/28=16 | | -2x^2+20x+112=0 | | 8^x+1-64=0 | | 6(1+3x)=-8(2x+5)-4 | | 259=u-669 | | –2(3x–1)=–6x–1 | | 4(10x+5)=4x-2 | | 7x/14=8x/6 | | h-336=265 | | 7x-17=6(x-2) | | 7(3x+2)=182 | | -23=g/17 | | 3(x+5)=7x+13-4x+2 | | 18=2-(y+6) | | 8(c–5)–3c=15 | | 3/2x+31/6=3/x+5 | | p/27=18 | | -27-4x=-5(x+5) |

Equations solver categories